Tinjauan Yuridis Mengenai Perangkat Undang-undang Pemilihan Umum - Harun Alrasid (Unisia, 2004)
The regulations on general election together with presidential election have changed along Indonesian history. For its more than a half of a century, the way general election has varied from very multiparty – very limited party and then multiparty. For this near coming general election, the representative will be chosen directly by constituents, a new system has been introduced, this is called by open-proportional. Again, this is the time, in which president will be chosen directly by people and separately from member of parliament election. The problem is. how far this, in its implementation will give significant change for the democratization in Indonesia. This article will bring to go through this analysis.